Artesunate/Amodiaquine Malaria Treatment for Equatorial Guinea (Central Africa) - Charle, Pilar (The American Society of Tropical Medicine and Hygiene, 2013)
The objectives of this study were: 1) to evaluate the safety and efficacy of combination artesunate (AS)/amodiaquine (AQ) therapy, and 2) to determine the difference between recrudescence and resistance. An in vivo efficacy study was conducted in Equatorial Guinea. A total of 122 children 6–59 months of age from two regional hospitals were randomized and subjected to a 28-day clinical and parasitological follow-up. A blood sample on Whatman paper was taken on Days 0, 7, 14, 21, and 28 or on any day in cases of treatment failure, with the parasite DNA then being extracted for molecular analysis purposes. A total of 4 children were excluded, and 9 cases were lost to follow-up. There were 17 cases of late parasitological failure, 3 cases of late clinical failure, and 89 cases of adequate clinical and parasitological response. The parasitological failure rate was 18.3% (20 of 109) and the success rate 81.70% (95% confidence interval [72.5–87.9%]). After molecular correction, real treatment efficacy stood at 97.3%. Our study showed the good efficacy of combination AS/AQ therapy. This finding enabled this treatment to be recommended to Equatorial Guinea's National Malaria Control Program to change the official treatment policy as of March 2008.